2019
DOI: 10.1126/scitranslmed.aav4523
|View full text |Cite
|
Sign up to set email alerts
|

Intein-mediated protein trans-splicing expands adeno-associated virus transfer capacity in the retina

Abstract: Retinal gene therapy with adeno-associated viral (AAV) vectors holds promises for treating inherited and noninherited diseases of the eye. Although clinical data suggest that retinal gene therapy is safe and effective, delivery of large genes is hindered by the limited AAV cargo capacity. Protein trans-splicing mediated by split inteins is used by single-cell organisms to reconstitute proteins. Here, we show that delivery of multiple AAV vectors each encoding one of the fragments of target proteins flanked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 51 publications
0
114
0
Order By: Relevance
“…DNA constructions were performed according to the principles of Gibson assembly 55 or using the BioBrick RFC [10] standard 56 , following standard molecular biology techniques. For the BioBrick RFC [10] standard FastDigest EcoRI, BcuI (SpeI), PstI, and XbaI enzymes were used (FD0274, FD1253, FD0614, and FD0684, respectively; Thermo Fisher). DNA fragments were generated by polymerase chain reaction (PCR) amplifications using primers with ≥18 bp overlaps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA constructions were performed according to the principles of Gibson assembly 55 or using the BioBrick RFC [10] standard 56 , following standard molecular biology techniques. For the BioBrick RFC [10] standard FastDigest EcoRI, BcuI (SpeI), PstI, and XbaI enzymes were used (FD0274, FD1253, FD0614, and FD0684, respectively; Thermo Fisher). DNA fragments were generated by polymerase chain reaction (PCR) amplifications using primers with ≥18 bp overlaps.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of inteins to seamlessly ligate two peptides or to selectively release the N-or C-extein portion has been extensively exploited for protein modification and purification, to produce intein-based biosensor and reporter systems, and even in gene therapy [6][7][8][9][10][11][12][13] .…”
mentioning
confidence: 99%
“…The use of AAV in human ROs is relatively limited at the moment, but studies have reported varying efficiency of transduction, which could be attributed to age of treatment, time of harvesting, vector tropisms, viral titre, the promotor used and sensitivity of detection of the transgene, e.g. antibody versus intrinsic fluorescence of a reporter (Gonzalez-Cordero et al, 2018, Tornabene et al, 2019, Quinn et al, 2019, Khabou et al, 2018. Here we demonstrate highly efficient transduction using an AAV2/5 vector with RP2 under the control of a CAG promoter.…”
Section: Discussionmentioning
confidence: 82%
“…AAVs are able to transduce post-mitotic rods and cones in mice following sub-retinal or intravitreal injection (Sarra et al, 2002) and in iPSC derived rod and cone photoreceptors in ROs with varying efficiency (Gonzalez-Cordero et al, 2018, Tornabene et al, 2019. In order to assess the ability of AAVs to deliver RP2 to deficient photoreceptors, RP2 KO ROs were transduced with AAV2/5.CAGp.RP2 (Fig.…”
Section: Aav2/5 Efficiently Transduces Retinal Organoids To Augment Rmentioning
confidence: 99%
“…Delivery of AAVintein vectors encoding for the ABCA4 protein in a mouse model of Stargardt disease resulted in significant amelioration of the phenotype. 99 Importantly, in a side-by-side comparison between the AAV-intein and dual AAV hybrid platforms, we found that the levels of AAV inteinmediated large protein reconstitution largely exceeded those achieved via AAV genome recombination by dual AAV vectors. 99 In addition, in the large pig retina we have found levels of AAV-intein-mediated protein reconstitution comparable to those achieved with a single AAV vector.…”
Section: Dual Aav-mediated Reconstitution Of a Large Genementioning
confidence: 85%